Epiphytic lichens and bryophytes of forest ecosystems in Tuscany (Central Italy) - Loppi, Stefano; Bonini, Ilaria; de Dominicis, Vincenzo (Cryptogamie Mycologie, 1999)
The distribution of epiphytic bryophytes and lichens on three species of trees (Quercus ilex, Quercus cerris and Fagus sylvatica, representing the forest ecosystems of central Italy at low, medium and high elevations, respectively) was examined with respect to host specificity and habitat differences. Although most species were host-specific, the results suggested that habitat characteristics are more important than phorophyte properties in determining the distribution of lichens and bryophytes. Factors affecting the diversity of the epiphytic flora were different for lichens and bryophytes. In the case of lichens, climatic parameters and forest monospecificity were important factors, whereas tree cover (i.e. shade) and to a certain extent the number of available trees seemed more important for bryophytes.
Keywords: distribution (voyant); epiphytic bryophytes; epiphytic lichens; forest ecosystems; Host specificity

Epiphytic lichens and bryophytes of forest ecosystems in Tuscany (Central Italy) - Loppi, Stefano; Bonini, Ilaria; de Dominicis, Vincenzo (Cryptogamie Mycologie, 1999)
The distribution of epiphytic bryophytes and lichens on three species of trees (Quercus ilex, Quercus cerris and Fagus sylvatica, representing the forest ecosystems of central Italy at low, medium and high elevations, respectively) was examined with respect to host specificity and habitat differences. Although most species were host-specific, the results suggested that habitat characteristics are more important than phorophyte properties in determining the distribution of lichens and bryophytes. Factors affecting the diversity of the epiphytic flora were different for lichens and bryophytes. In the case of lichens, climatic parameters and forest monospecificity were important factors, whereas tree cover (i.e. shade) and to a certain extent the number of available trees seemed more important for bryophytes.
Keywords: distribution (voyant); epiphytic bryophytes; epiphytic lichens; forest ecosystems; Host specificity

Vegetation of tuscan ultramafic soils in relation to edaphic and physical factors - Chiarucci, Alessandro; Robinson, Brett H.; Bonini, Ilaria; Petit, Daniel; Brooks, Robert R.; Dominicis, Vincenzo (Folia Geobotanica, 1998)
Vegetation and soil sampling were carried out in 80 plots located in five different ultramafic (serpentine) sites of Tuscany, central Italy. The physical and chemical features of each plot. were determined and the species composition and cover recorded. The exchangeable fraction of soil metals was analysed because it gives a measure of their concentrations available to plants. The plots were classified by cluster analysis and ANOVA was used to compare the environmental variables of the groups of plots. Canonical correspondence analysis was used to detect the principal factors for gradients of species composition within the plant communities. A higher content of exchangeable metals was found under the more evolved and structured plant communities, suggesting that serpentine vegetation of Tuscany is not strongly limited by soil metals, such as chromium, cobalt, nickel and magnesium, typically associated with ultramafic soils. The low nutrient content of the soils and drought stress mainly due to topographical features, appear to have a more significant role in determining the typical scattered vegetation of the Tuscan ultramafics.
Keywords: canonical correspondence analysis; Drought; serpentine; soil features; species diversity; vegetation ecology